2001
DOI: 10.1083/jcb.200106070
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of adherent cells by recruitment of caspase-8 to unligated integrins

Abstract: Integrin-mediated adhesion promotes cell survival in vitro, whereas integrin antagonists induce apoptosis of adherent cells in vivo. Here, we demonstrate that cells adherent within a three-dimensional extracellular matrix undergo apoptosis due to expression of unligated integrins, the β subunit cytoplasmic domain, or its membrane proximal sequence KLLITIHDRKEF. Integrin-mediated death requires initiator, but not stress, caspase activity and is distinct from anoikis, which is caused by the loss of adhesion per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
396
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(421 citation statements)
references
References 67 publications
19
396
5
1
Order By: Relevance
“…These 'non-liganded integrins,' which are either unligated or occupied with a soluble antagonist, not only disrupt survival signaling but also actively induce apoptosis, hence supporting the view of integrins as DRs (Stupack et al, 2001) (Figure 2 and Table 1).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 55%
See 2 more Smart Citations
“…These 'non-liganded integrins,' which are either unligated or occupied with a soluble antagonist, not only disrupt survival signaling but also actively induce apoptosis, hence supporting the view of integrins as DRs (Stupack et al, 2001) (Figure 2 and Table 1).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 55%
“…Indeed, Stupack et al (2001) elegantly showed that integrins, as DRs, trigger apoptosis through recruitment of caspase 8.…”
Section: Proapoptotic Signaling By Drsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, apoptosis does occur under these circumstances. 15,[58][59][60] Cell surface expression of integrins in the antagonized 60 or unligated state 58 can promote apoptosis among otherwise attached and 'spread' cells.…”
Section: Antagonized Integrins Promote Apoptosis Of Adherent Cellsmentioning
confidence: 99%
“…In cells in which most of the integrins are ligated, pro-survival signals were reported whereas pro-apoptotic signals were found in unligated cells [50,51]. The role of heparin in this complex network will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%